Edukasi Pengontrolan Kecemasan pada Remaja Menggunakan Terapi Hipnosis Lima Jari - Prima Dian Furqoni; Rahma Elliya; Triyoso Triyoso; Rika Juana; Yanti Fitria; Yunidha Puspita Sari; Najamuddin Dalimunthe (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2025)
Anxiety in adolescents in Indonesia is an increasingly pressing mental health problem. According to the National Adolescent Mental Health Survey (I-NAMHS) conducted in 2022, around 15.5 million Indonesian adolescents aged 10 to 17 years experienced mental health problems in the past 12 months. Various factors, such as academic pressure, bullying, problems in family and peer relationships, and the influence of social media, often cause anxiety in adolescents. Five-finger hypnotherapy is a therapy that uses five fingers to help clients change their perception of their anxiety levels without the effects of dependency. Using five-finger hypnosis, combine the index finger and thumb to imagine a healthy body, the middle finger to imagine a loving and caring person, the ring finger to imagine achievements, awards, and praise that have been experienced, and the little finger to imagine the most beautiful place ever visited. The purpose of this activity is to increase adolescent knowledge and skills to overcome anxiety with five-finger hypnosis. The socialization method in the form of lectures and questions and answers is used in this activity with leaflets and flip charts. The results of the respondents' activities were very enthusiastic about the material presented and there were several respondents who asked questions. The conclusion of this educational activity was successful in increasing the knowledge and skills of adolescents in overcoming anxiety.